Photoprotective mycosporine-like amino acids in different organs of Baltic flatfish species revealed by targeted and untargeted metabolomics analyses - Hammerle, Fabian J.; Schöpf, Romina; Karg, Cornelia A.; Krumme, Uwe; Gostner, Johanna M.; Karsten, Ulf; Ganzera, Markus (Frontiers in Marine Science, 2025)
Coastal marine organisms are often exposed to high levels of biologically harmful ultraviolet radiation (UVR), the most photochemically reactive waveband of sunlight. It is well known that marine organisms at higher trophic levels, such as fish, enhance their UV protection by accumulating UV-protective metabolites from their diet, as primary producers can effectively synthesize these compounds. Among the best studied natural UV-sunscreens in marine organisms are mycosporine-like amino acids (MAAs). They are known for their high molar extinction coefficients in the UVR-region along with pronounced photo- and thermal stability. In the present study we investigated the qualitative and quantitative MAA distribution in organs (eyes, gills, heart, intestine, kidneys, liver, skin, and stomach) of three flatfish species from the Baltic Sea, the benthivorous European flounder (Platichthys flesus) and European plaice (Pleuronectes platessa), and the piscivorous turbot (Scophthalmus maximus), using state-of-the-art analytical methods. Most of the analyzed organ samples contained the MAAs palythine, asterina-330, porphyra-334, usujirene, and palythene at concentrations sufficient for reliable detection and quantification using an established HPLC-UV method. Additionally, in a few samples also shinorine and mycosporine-methylamine-threonine were found. The highest MAA contents (0.04 to 0.25 mg g-1 dry weight) occurred in the eyes of the three fish species, while the other organs exhibited much lower but still detectable concentrations. Our data support the assumed trophic transfer of MAAs from primary producers via the food web to fish. For the first time we show that MAAs are not only found in the eyes but also in internal organs that possibly represent transfer points from the digestive tract to UV-sensitive tissues. The underlying mechanisms are, however, still unknown.